Unusually Large Lattice Mismatch‐Induced Optical Behaviors of Au@Cu–Cu2O Core–Shell Nanocrystals with Noncentrally Located Cores. (6th June 2018) - Hsia, Chi‐Fu; Chang, Chia‐Hao; Huang, Michael H.
Abstract: To extend the optical property characterization of metal–Cu2 O polyhedra, 50 nm Au@Cu cubic cores are used to fabricate Au@Cu–Cu2 O core–shell cubes, octahedra, and rhombic dodecahedra with tunable sizes. Despite the unusually large lattice mismatch of 15.1% between Cu and Cu2 O, fine adjustment in the volumes of reagents introduced allows the formation of these heterostructures. To relieve the lattice strain, the metal cores are essentially never found to locate at the particle center, and slight lattice spacing shifts are recorded. Although efforts are made to reduce the heterostructure sizes, the Cu2 O shells are generally too thick to reveal surface plasmon resonance (SPR) absorption band from the metal cores. Only the Au@Cu–Cu2 O cubes with many cores located near the particle corners show observable SPR band red‐shift, but UV–vis spectra of all particle shapes are still dominated by Cu2 O absorption and light scattering bands. Au@Cu–Cu2 O cubes consistently show the most red‐shifted absorption bands than those of octahedra resulting from the optical facet effects. Abstract : Size‐tunable Au@Cu–Cu2 O cubes, octahedra, and rhombic dodecahedra with noncentrally located metal cores are synthesized. The metal cores are not centrally located because of the ultralarge lattice mismatch between Cu and Cu2 O. Only Au@Cu–Cu2 O cubes display some plasmonic absorption band because of the partially thinner Cu2 O shells.